10 years’ cultural variation of Croatia from pre to post accession: the changed value and unchanged cultural position - Wang, Chunyan; Bakota, Ivica; Buljan, Ivana; Shang, Yuhong (Frontiers in Sociology, 2025)
IntroductionCroatia’s accession to the European Union (EU) in 2013 completed its institutional integration; however, the alignment of its social and cultural values with those of other EU member states remains an ongoing process.MethodsUtilizing Hofstede’s cultural dimensions framework and data from rounds 5 and 10 of the European Social Survey (ESS), this study examines the evolution of Croatia’s value orientations from 2010 to 2020 and assesses whether the cultural value gap between Croatia and other EU members has narrowed.ResultsThe study identifies significant cultural shifts: the decline in Masculinity, Uncertainty Avoidance, and Power Distance indexes, alongside an increase in Individualism. These shifts are in the same direction with those of the old EU members. However, despite these changes, Croatia’s cultural value distance from other EU members has largely remained constant. Particularly, Power Distance index in Croatia is persistently higher than the average level.DiscussionThese findings suggest that the EU should strengthen its common values within the newly accessed members. Policies aimed at encouraging participation in EU-wide cultural and economic projects may also bridge cultural divides. The study contributes to an understanding of cultural change in post-transition societies and their implications for EU integration.